1990
DOI: 10.1128/aem.56.4.1135-1139.1990
|View full text |Cite
|
Sign up to set email alerts
|

Shiga-like-toxin-producing Escherichia coli in retail meats and cattle in Thailand

Abstract: Specific DNA probes were used to identify Shiga-like toxin I (SLT I)and SLT II-producing Escherichia coli in vegetables, meats, cattle, and farm animals in Thailand. SLT-producing E. coli was isolated from 9% of market beef specimens, from 8 to 28% of fresh beef specimens at slaughterhouses, and from 11 to 84% of fecal specimens from cattle. Animals were frequently infected with several different SLT-producing E. coli types that hybridized with either the SLT I, SLT II, or both SLT probes. Of 119 SLT-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Our observation that 32 of 36 VTEC isolates from calves in north-central states hybridized with only the VT 1 probe is consistent with reports that most of the non-O157:H7 bovine VTEC isolated by laboratories located in England were positive for only VT1 (Smith et al, 1988;Dorn et al, 1989;Scotland et al, 1990). However, few of the non-O 157 :H7 VTEC isolated from healthy cattle (usually mature) hybridized with only the VT 1 probe in Germany and in Thailand, 5% and 14%, respectively (Montenegro et al, 1990;Suthienkul et al, 1990). Serotype O 157:H7 and other serotypes isolated from human HC and HUS cases usually produce SLT II alone or both SLT I and II, but much less frequently SLT I alone Dickie et al, 1989;Ostroff et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observation that 32 of 36 VTEC isolates from calves in north-central states hybridized with only the VT 1 probe is consistent with reports that most of the non-O157:H7 bovine VTEC isolated by laboratories located in England were positive for only VT1 (Smith et al, 1988;Dorn et al, 1989;Scotland et al, 1990). However, few of the non-O 157 :H7 VTEC isolated from healthy cattle (usually mature) hybridized with only the VT 1 probe in Germany and in Thailand, 5% and 14%, respectively (Montenegro et al, 1990;Suthienkul et al, 1990). Serotype O 157:H7 and other serotypes isolated from human HC and HUS cases usually produce SLT II alone or both SLT I and II, but much less frequently SLT I alone Dickie et al, 1989;Ostroff et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
“…The higher prevalence of SLT IIE. coli than SLT I E. coli infections among mature cattle (Montenegro et al, 1990;Suthienkul et al, 1990) might result in more passive transfer of SLT II antibody than SLT I antibody, resulting in lower incidence of clinical illness due to SLT II producing VTEC strains in calves. This hypotheses should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of a total of 98 stool samples from slaughtered cattle and 79 diarrhoeic faeces from the calves revealed the presence of sorbitol-negative and b-D-glucuronidase-negative E. coli. Slaughtered cattle and diarrhoeic calves were sampled because previous studies indicated that these animals are more likely to shed STEC than healthy cattle in farm condition (Suthienkul et al 1990;Zhao et al 1995;Blanco et al 1996;Armstrong et al 1996;Chapman et al 1997). Serotyping of the E. coli isolates identified E. coli serotype O157 strains from two (2.04%) slaughtered cattle and six (7.59%) calves.…”
Section: Occurrence Of Escherichia Coli O157mentioning
confidence: 99%
“…We con¢rmed that the AP-PCR patterns of these strains were reproducible under the present experimental condition and found that none of the ¢ve Thai strains showed an identical pattern with any of the Malaysian, Japanese, and Korean strains and EDL933 (data not shown). Other workers did not detect E. coli O157 in retail meats and cattle in an earlier study conducted in Thailand [7]. However, the genetic ¢ngerprinting data suggest that the ¢ve Thai strains of E. coli O157 may not have been introduced recently from the neighboring area in Malaysia.…”
Section: Characterization and Comparison Of The Isolated O157 Strainsmentioning
confidence: 86%
“…However, isolation of E. coli belonging to serogroup O157 has rarely been reported in Asian countries except Japan ; isolation of E. coli O157 from clinical sources in India, China, Korea, and Hong Kong has been brie£y reported [1,4^6]. E. coli of O157 serogroup was not detected in a survey for Stx-producing E. coli in retail meat and farm animals in Thailand, which was reported in 1990 [7]. Recently, beef marketed in Malaysia was shown to be contaminated by E. coli O157:H7 [8].…”
Section: Introductionmentioning
confidence: 99%